With sincere and humble devotedness to Her Majesty's service [...] with honour and success, in |the ||war they have undertaken in behalf of Turkey and the just right of nations, this map of the present seat of war, originally founded, and constructed, on the basis of remarkable Russian materials by the staff of the Austrian quartermaster-general at the command of field marshall prince Schwarzenberg, has been exactly reproduced (200 copies in ten days) (John Petheram, 1854)
Turkish government [ark. 4].
under the direction of major Thomas Best Jervis [...] ; John Petheram.
Keywords: mapy wojskowe; Turcja; Kartografia; w kartografii; Bosfor (Turcja); Azja Mniejsza; Pilos (Grecja); Grecja; Izmir (Turcja); Prevesa (Grecja); Dardanele (Turcja); Butrini (Albania); Belgrad (Serbia); Rodos (Grecja; wyspa); Korynt (Grecja)